2013
DOI: 10.1007/s00253-013-5253-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel multispecies microbial consortia involved in lignocellulose and 5-hydroxymethylfurfural bioconversion

Abstract: To develop a targeted metagenomics approach for the analysis of novel multispecies microbial consortia involved in the bioconversion of lignocellulose and furanic compounds, we applied replicated sequential batch aerobic enrichment cultures with either pretreated or untreated wheat straw as the sources of carbon and energy. After each transfer, exponential growth of bacteria was detected using microscopic cell counts, indicating that the substrate was being utilized. In batch, the final bacterial abundances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 52 publications
5
104
1
Order By: Relevance
“…First, we isolated and identified a new strain, R. ornithinolytica BF 60, that can efficiently produce FDCA from 5-HMF, which is a basic furanic compound, from biorenewable sources. It was recently reported that Raoultella species are members of lignocellulose-degrading communities and play an active role in the response to furanic compounds (21). For the production of fine chemicals and pharmaceutical compounds, whole-cell-based biotransformation processes have been developed through process optimization and engineering of cellular metabolic pathways (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…First, we isolated and identified a new strain, R. ornithinolytica BF 60, that can efficiently produce FDCA from 5-HMF, which is a basic furanic compound, from biorenewable sources. It was recently reported that Raoultella species are members of lignocellulose-degrading communities and play an active role in the response to furanic compounds (21). For the production of fine chemicals and pharmaceutical compounds, whole-cell-based biotransformation processes have been developed through process optimization and engineering of cellular metabolic pathways (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, members of other phyla were also important for the anaerobic digestion process, e.g., the presence of Citrobacter and Escherichia in the reactors may be responsible for lignin degradation [60,61], and Spirochaeta is involved in cellulose degradation [54].…”
Section: Characteristics Of Bacterial Communitymentioning
confidence: 99%
“…The use of microbial consortia for industrial production of bio-products has not yet been studied to any great extent (82). The main advantage of using a consortia co-culture system is the flexibility that is absent in mono-cultures systems of individual strains for the rational design of secretome compositions (54).…”
Section: Co-culture Fermentations Using Avicel Cellulosementioning
confidence: 99%
“…The main advantage of using a consortia co-culture system is the flexibility that is absent in mono-cultures systems of individual strains for the rational design of secretome compositions (54). Microbial consortia, also known as co-fermentation systems, have been studied due to their usefulness in bio-processing (83), moreover consortia can consist of multiple species or a single species with different engineered lines (82).…”
Section: Co-culture Fermentations Using Avicel Cellulosementioning
confidence: 99%